2016
DOI: 10.1097/mnm.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of pretreatment 18F-FDG uptake with clinicopathological factors and prognosis in patients with newly diagnosed diffuse large B-cell lymphoma

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
(39 reference statements)
3
10
1
Order By: Relevance
“…We also recorded the SUV max value of patients using PET-CT scan. PET-CT is the recommended imaging method to be used clinically when evaluating lymphoma patients [25, 26], and the SUV max value showed correlation with prognosis and lymphoma recurrence [2729]. Our data showed that RasGRP4 expression was positively correlated with the SUV max value, supporting the association with high-risk IPI groups, further demonstrating the prognostic value of RasGRP4.…”
Section: Discussionsupporting
confidence: 68%
“…We also recorded the SUV max value of patients using PET-CT scan. PET-CT is the recommended imaging method to be used clinically when evaluating lymphoma patients [25, 26], and the SUV max value showed correlation with prognosis and lymphoma recurrence [2729]. Our data showed that RasGRP4 expression was positively correlated with the SUV max value, supporting the association with high-risk IPI groups, further demonstrating the prognostic value of RasGRP4.…”
Section: Discussionsupporting
confidence: 68%
“…A Chinese study on a group of lymphoma patients showed that post-treatment SUVmax values were significantly correlated with post-treatment CRP values [36]. By contrast, a previously mentioned study demonstrated that baseline SUVmax was weakly correlated with CRP (r = 0.215, p = 0.011) [34].…”
Section: Discussionmentioning
confidence: 94%
“…The authors of a meta-analysis concerning correlations between FDG uptake and Ki67 reported significant heterogeneity in HNC cases [33]. Furthermore, pretreatment SUVmax was significantly higher in patients with enhanced Ki67 expression in comparison to those with low Ki67 expression, but the study concerned diffuse large B-cell lymphoma [34]. Surov et al reported that SUVmax was moderately correlated with Ki67 expression and therefore cannot be used as a surrogate marker for tumor proliferation [35].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical roles of FDG PET/CT scan in diagnosis, staging, monitoring of treatment and prediction of prognosis in patients with lymphoma have been reported [ 7 - 11 ]. The maximal SUV of the primary tumor has been previously demonstrated to be of prognostic values, because of easy accessibility and high reproducibility [ 12 , 13 ]. However, maximal SUV solely recorded intensity of FDG uptake in the most aggressive cells, without reflecting the volumetric concept.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized uptake value (SUV) is the most commonly used semi-quantitative parameter in FDG PET/CT. Higher maximal SUV in the lesion has been proved to be of prognostic significance in patients with DLBCL [ 12 , 13 ]. Beyond SUV, with the development of software programs, metabolic tumor volume (MTV) and total lesion glycolysis (TLG) have recently been found to play an important role in the prediction of patient outcomes.…”
Section: Introductionmentioning
confidence: 99%